Spectrally Resolved Ultraviolet (UV) Absorption Cross-Sections of Alkali Hydroxides and Chlorides Measured in Hot Flue Gases. Issue 9 (September 2018) - Weng, Wubin; Leffler, Tomas; Brackmann, Christian; Aldén, Marcus; Li, Zhongshan
Spectrally resolved ultraviolet (UV) absorption cross-sections of gas-phase sodium chloride (NaCl), potassium hydroxide (KOH), and sodium hydroxide (NaOH) were measured, for the first time, in hot flue gases at different temperatures. Homogenous gas-phase NaCl, KCl (potassium chloride), NaOH, and KOH at temperatures 1200 K, 1400 K, 1600 K, and 1850 K were prepared in the post-flame zone of laminar flames by seeding nebulized droplets out of aqueous solution of corresponding alkali species. The amount of droplets seeded into the flame was kept constant, so the relative concentration of different alkali species can be derived. The broadband UV absorption cross-section of KCl vapor reported by Leffler et al. was adopted to derive the absorption cross-section curves of NaCl, NaOH, and KOH with the corresponding measured spectrally resolved absorbance spectra. No significant changes in the spectral structures in the absorption cross-sections were found as the temperature varied between 1200 K and 1850 K, except for NaOH at around 320 nm. The difference between the absorption spectral curves of alkali chlorides and hydroxides is significant at wavelengths above 300 nm, which thus can be used to distinguish and obtain the concentrations of alkali chlorides and hydroxides in the broadband UV absorption measurements.